Green Milk From Contented Cows: Is It Possible? - Webster, John (Frontiers in Animal Science, 2021)
The dairy industry is open to criticism on several fronts: obesity and ill health among the affluent, high demand for crops that could be consumed more sustainably and more equitably by ourselves, environmental damage and climate change, and abuse of animal welfare through production diseases and denial of normal patterns of behaviour. All these criticisms are valid. It is necessary therefore to examine in depth the nature and extent of specific problems to see which, if any, are inevitable, which can be mitigated and which can be avoided altogether. Dairy cattle, like all ruminants, can be sustained wholly, or in part on complementary feeds; grasses and crop residues that cannot be fed directly to humans. Fed appropriate diets dairy cows can produce more energy and protein for human consumption than they consume. The greenhouse gas, methane is an inevitable consequence of rumen fermentation. High yielding cows in confinement produce less methane per litre of milk. There is some scope for reducing methane production through manipulation of rumen fermentation but the impact is likely to be small. The most serious welfare abuses can be linked to genetic and management strategies designed to maximise milk yield from individual cows. These manifest in production diseases and metabolic exhaustion, both leading to premature culling. All these problems; too much milk, too much food waste, too much methane, too many stressed cows, are matters of degree. The poison is in the dose. Thus, solutions will not come from radical advances in biological science but public and political exercises in moderation.